Combined Effects of Curing Temperatures and Alkaline Concrete on Tensile Properties of GFRP Bars - Wen-rui Yang; Xiong-jun He; Kai Zhang; Yang Yang; Li Dai (International Journal of Polymer Science)
A significant number of studies have been conducted on the tensile properties of GFRP bars embedded in concrete under different environments. However, most of these studies have been experimentally based on the environmental immersion test after standard-curing and the lack of influence on the tensile properties of GFRP bars embedded in concrete during the curing process of concrete. This paper presents the results of the microscopic structures through scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and tensile properties of GFRP bars, which were employed to investigate the combined effects of curing temperatures and alkaline concrete on tensile properties of GFRP bars. The results showed that the higher curing temperature aggravated the influence of the alkaline concrete environment on GFRP bars but did not change the mechanisms of mechanical degradation of the GFRP bars. The influence of different curing temperatures on the tensile strength of GFRP bars was different between the bare bar and bars in concrete. Finally, the exponential correlation equation of two different test methods was established, and the attenuation ratio of the tensile strength of GFRP bars embedded in concrete under different curing temperatures was predicted by the bare test.